Advancements in Understanding Catalyst Reconstruction During Electrochemical CO2 Reduction - Woosuck Kwon; Dohun Kim; Yujin Lee; Jinoh Jung; Dae‐Hyun Nam (Exploration)
ABSTRACT Electrochemical CO2 reduction reaction (CO2RR) has received great attention to solve CO2‐ induced global warming and carbon neutrality. It is essential to enhance the electrochemical CO2RR selectivity, activity, and long‐term stability for sustainable manufacturing of specific chemicals via CO2RR. To produce multi‐carbon (C2+) chemicals, Cu‐based heterogeneous catalysts have been developed in terms of defect engineering, morphological design, and facet control. Despite the substantial efforts for the design of efficient Cu‐based heterogeneous catalysts, there exist inevitable structural changes of catalysts with continuous dissolution and redeposition during CO2RR. This reconstruction modifies the as‐synthesized catalysts into an unpredictable structure and leads to changes in active site. Here, we review the reconstruction of Cu‐based catalysts during CO2RR, which occurs via continuous dissolution and redeposition process. This includes fundamental principles of reconstruction and the effect of microenvironment on reconstruction during CO2RR. We offer research progress about the reconstruction of Cu‐based electrocatalysts, analysis methodologies to track the reconstruction, and the insight to improve the activity, selectivity, and stability of CO2RR. We provide perspective to understand and harness the reconstruction for the development of efficient CO2RR catalysts.